2006
DOI: 10.1055/s-2006-946678
|View full text |Cite
|
Sign up to set email alerts
|

Two New Phenolic Glycosides from the Barks ofHydnocarpus annamensisand their Anti-Inflammatory and Anti-Oxidation Activities

Abstract: Two new phenolic glycosides 1 and 2 were isolated from the barks of Hydnocarpus annamensis, along with eighteen known compounds. The structures of all compounds were deduced using spectroscopic methods. Anti-inflammatory and anti-oxidation activities were evaluated. Among the isolates, compounds 1, 5, 15 and 17 exhibited COX-2 inhibitory activities, with an inhibitory rate of 60.3 - 63.4 % at 10 microM. Compounds 7, 12, 13 and 20 showed anti-oxidation capacities in the DPPH free-radical assay, with a scavengin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Together, these results question whether the G glycerol units are solely due to oxidation. Alternatively, guaiacylglycerol might be synthesized intracellularly, as it was isolated as only one enantiomeric form, the D-threo-isomer, from Zantedeschia aethiopica (Della Greca et al, 1998), and guaiacylglycerol glucosides were detected in leaves of Juniperus phoenicea (Comte et al, 1997), in roots and rhizomes of Sinopodophyllum emodi (Zhao et al, 2001), in stems of Hydnocarpus annamensis (Shi et al, 2006) and Xylosma controversum (Xu et al, 2008), and in leaves and branches of Camellia amplexicaulis (Tung et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Together, these results question whether the G glycerol units are solely due to oxidation. Alternatively, guaiacylglycerol might be synthesized intracellularly, as it was isolated as only one enantiomeric form, the D-threo-isomer, from Zantedeschia aethiopica (Della Greca et al, 1998), and guaiacylglycerol glucosides were detected in leaves of Juniperus phoenicea (Comte et al, 1997), in roots and rhizomes of Sinopodophyllum emodi (Zhao et al, 2001), in stems of Hydnocarpus annamensis (Shi et al, 2006) and Xylosma controversum (Xu et al, 2008), and in leaves and branches of Camellia amplexicaulis (Tung et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…HMBCs (l " Fig. 2) from H-6′′ to C-1′′, C-5′′, and a carboxyl (δ C = 172.6); from H-1′′ to C-4′′, C-5′′, and C-3′′; and from H-7′′ to C-3′′, C-4′′, C-5′′, and C-6′′ constructed a highly oxygenated lactone bridge ring (2-oxabicyclo [2,2,1]heptan-3-one-4,5,6-trihydroxy-5-formacyl), and the key HMBC from H-7 to another carboxyl carbon (δ C = 172.6) established this lactone ring moiety attached at C-7. The position of the hydroxy group at the quaternary carbon (C-4′′) lying at the bridgehead suggested its relative β-configuration, and the coupling constants J H-6′′/H-1′′ = 2.0 indicated that they have a large dihedral angle between 0°and 90°, suggesting that C-6′′-OH and the carboxyl (C-3′′) were in the trans orientation, which is in accordance with the obvious correlation of H-6′′ with H-1′′, as well as with the weak correlation of H-6′′ with H-7′′α observed in the NOESY spectrum of 3.…”
Section: Hr-esi-ms Analysis Of Compound 3 Gave An [M + H]mentioning
confidence: 99%
“…We previously reported the phenolic and flavonoid glycosides from the leaves of S. chinensis [5] and some known compounds from its stems [8]. Herein, we describe the isolation and structure elucidation of three new phenolic glycosides, scolochinenosides C-E (1)(2)(3), and a new triterpenoid scolopianate A (4) (l " Fig. 1), together with 15 known compounds in a continued investigation toward the stems.…”
mentioning
confidence: 94%
“…The Bark, seed, leaf and stem of Hydnocarpus have been used for treating leprosy and other skin disorders for thousands of years in India, China and southeast Asia (Cole and Cardoso, ; Cole and Ht, ; Nayer, ; Chellappandian et al ., ). In recent pharmacological studies, extracts of Hydnocarpus demonstrated a variety of in vitro and in vivo activities including anti‐diabetic (Jong‐Anurakkun et al ., ; Lee et al ., ) anti‐inflammatory (Wang, ), hypolipidemic (Sharma and Hall, ), antimicrobial (Bueno Pérez et al ., ) and antioxidant activities (Shi et al ., ), and this has attracted much attention. Furthermore, significant inhibitory activity on the growth of the human glioma cell line U251 has been reported for the ethanol extract of Hydnocarpus hainanensis , and its use as an antitumor drug has been suggested.…”
Section: Introductionmentioning
confidence: 99%